عوامل التطور والتنظيم الصحي للثورة التحريرية (1956 -1962 - مرجع, عائشة (جامعة الوادي University of Eloued, 2017)
يعالج هذا المقال موضوع في غاية الأهمية ،اذ يبرز تطور التنظيم الصحي للثورة التحريرية ،ذلك أن الثورة عاشت في مرحلتها الأولى (1954-1956) نقص فادح في توفر الخدمات الصحية واعتمادها على الوسائل التقليدية ،ونظرا لتطور الأحداث وزيادة عدد الجرحى والمرضى في صفوف المجاهدين و المدنيين على حد سواء ،كان لابد من تأسيس تنظيم صحي ،هذا الأخير ساهم في تأسيسه وتطويره عوامل عدة يمكن طرح أهمها كالتالي :بداية بالإضراب اللامحدود للطلبة الجزائريين 19 ماي 1956 ،الذي زود الثورة بإطارات طبية متعددة من أطباء وصيادلة وممرضين ،ثم مؤتمر الصومام 20 أوت 1956 ،الذي عمل على تنظيم الثورة في جميع الجوانب ،ليحضى جانب الصحة هو الآخر بمجموعة من القوانين والقواعد التنظيمية ،كما كان لتأسيس الهلال الأحمر الجزائري دور مهم في الصحة بتوفير الأدوية والعلاج والتكوين ،ولا يمكننا صرف النظر عن الدعم الخارجي للصحة سواء الدول الأجنبية أو العربية والقواعد الخلفية التي كان لها دور جد مهم في إنعاش القطاع الصحي للثورة التحريرية ،وكذا المنظمات الانسانية. This article deals with a very important topic .It shows the revolution of the health organization of the Algerian war of independence .In fact , first phase of that revolution ,which lasted from1956 to 1962,head seen a fatal deficiency in the availability of health service because of the reliance on the traditional methods .After the growing of the war events and the increase in the number of the sounded and the injured in the ranks of the fighters and civilians as well ,it was necessary to establish a well-organized sector for health .this letter was achieved and developed due to many factors. First ,the start of unlimited strike ,lead by the Algerian students on the 19th of my 1956,provided the revolution with multiple medical aid rich as doctors ,pharmacists and nurses .Second ,the appearance of the Soumam congress in August 20th,1956 gave a new order and well-structured organization in various aspects like "health" .In addition to this ,the establishment of the Algerian red crescent had played an Important role as it provided medicines ,treatments and training for soldiers .Most importantly ,it' s impossible to deny the external support which came from either the foreign countries or the Arabe ones in addition to the "rear" bases and the humanitarian organizations that had an active role in enhancing the health field of the Algerian revolution
Keywords: الثورة ، الصحة ، الهلال الأحمر الجزائري ، الأطباء ، الجرحى ، المراكز الصحية